Comparison Between Urinalysis Results and Self-Reported Heroin Use Among Patients Undergoing Methadone Maintenance Treatment in China. (24th August 2017) - Li, Li; Liang, Li-Jung; Lin, Chunqing; Feng, Nan; Wu, Zunyou
ABSTRACT: Background : The validity and concordance of two main measures of drug use behavior, self-report and urinalysis, has long been discussed. More understanding is needed about the underlying factors associated with discordance between these two methods. Objectives : Describe the pattern and associated factors of discordance between self-reported heroin use and the urinalysis results of opiate use among methadone maintenance therapy (MMT) patients in China. Methods : A total of 2, 448 MMT patients from 68 clinics in five provinces of China participated in a survey, which collected information on demographics, drug use and MMT-related factors, depressive symptoms, and drug avoidance self-efficacy. The most recent urine morphine test result was obtained from medical records and compared with self-reported heroin use. Participants who had urinalysis within 14 days of the survey were included in the analysis. Results : Among the 1, 092 participants, 70 (6.4%) self-reported heroin use and 195 (17.9%) had positive urinalysis results. The over-reporters group had significantly higher education, and the under-reporters had significantly higher level of drug-avoidance self-efficacy and lower level of depressive symptoms. Among the participants who either self-reported heroin use or had positive urinalysis results, being young, having higher education, and having lower level of depressive symptoms were associated with discordance between self-reports and urinalysis results. Conclusion : The combination of both measures in assessing drug use behavior seems necessary. The validity of self-report should be considered differently based on demographic and psychosocial characteristics.